Clusterization of reasons for bankruptcy of enterprises - Giriūnas, Lukas; Mackevičius, Jonas; Valkauskas, Romualdas (Buhalterinės apskaitos teorija ir praktika, 2013)
Bankruptcies of enterprises are among the most common events in the market economy. They cause a lot of negative effects not only for the company and its employees, but also for other companies and institutions, the state and society. Although the researchers have examined the reasons for bankruptcy, there is no list of the signs clearly indicating the likelihood of bankruptcy. Or such list is impossible due to the fact that causes of bankruptcy are related to the complex and constantly changing external environment of the company. That is why various features are only the symptoms pointing to the fact that the company is in danger of going bankrupt. It should be mentioned that some signs indicate that the company may face a number of difficulties, including bankruptcy, if the company’s management will not take appropriate action to eliminate causes of bankruptcy or to adjust to them. Reasons for bankruptcy can be divided into: 1) internal, 2) external. External reasons are such reasons that cannot be affected by company’s executives because they do not depend on the executives’ will. Internal reasons are such reasons that depend on the company’s executives and their level of professionalism, initiative, and ability to lead and to make the right decisions. In order to take the lowest risk, company’s analysts should monitor and investigate all internal and external causes. As it has been already mentioned, there are many internal and external reasons for companies’ bankruptcy but it is not clear which are the most important ones. To answer this question the authors of this article, on the basis of Lithuanian and foreign scientific research, have compiled a theoretical list and the tree of the internal and external causes of bankruptcy. The tree and its components are improved with clusters of reasons for bankruptcy of enterprises.
Keywords: bankruptcy; reasons for bankruptcy; tree of bankruptcy reasons; clustering